Impact of Transformational Leadership Style on Public Sector’s Performance in Nigeria: A Focus on Niger State Ministry of Education - Yohana, Chidawa; Joel, Maichibi Haruna (NIU Journal of Social Sciences; Vol 9 No 4 (2023): NIU Journal of Social Sciences, Vol. 9 No. 4, December 2023, 2023)
Leadership is said to be the fulcrum of every organization, Effective leadership style encourages better performance in organization. The Transformational leadership style is adopted to enhance the motivation, morale and job performance of subordinates this is done through a variety of mechanisms in the Ministry of Education Niger State. This study addresses two objectives which includes: impact of transformational leadership style on Job performance in Niger State Ministry of Education and the examination of the extent in which the attitudinal behaviour of the leadership and subjects in the ministry affect the job performance. The study adopted both primary and secondary sources of data collection using questionnaires and interviews to acquire relevant information for the study, secondary data were sourced from print materials to complement the primary data. The findings include, the transformational leadership in Educational Ministry typically perform for distinctive behavior that lead the organization to higher and greater achievement. The behavior is also known as four (I’S), which enable transformational leadership to discharge innovative characteristics for actualization of ministerial objectives. Leaders’ behavior influence followers and inspire them to perform beyond their perceived capabilities while accomplishment of target of the ministry is achieved through collective responsibility and relationship between leadership and subordinate. It was recommended that the modern organization being it public or private should focus and encourage transformational leadership style to ease and enhance positive change in every society, moreover, leaders and subjects in Niger State Education Ministry should work more co-operatively and ensure effective communication and feedback mechanisms in all their dealings while staff promotion in the ministry should base on merit and performance. However, organization that embark on transformational leadership encourage coordination and effective service delivery through dedication and commitment.  Keywords: Leadership, Transformation, Ministry, Education